Two lenses on texts and practices: Analysing remixing practices across timescales - Øystein Gilje (Stockholm University Press, 2011)
Scholars in several fields of research have increasingly started to pay attention to how young people remix media content on a wide range of sites and for various reasons. This article brings together socio-cultural and multimodal perspectives in order to provide a refinement of our understanding of remixing as a literacy practice. The author argues for two analytical lenses in order to understand how semiotic artefacts are negotiated by students and remixed in situ. By using the notion of timescale as a lynchpin between multimodal and socio-cultural analysis, the author seeks to understand how remixing work on different timescales. The author proposes the term Remixing to denote the development of culture across time, and the term remixing to denote a practice that can be empirically examined through close analysis of artefacts and activities in literacy practices.